The Voice of Music: Conversations with Composers of Our Time - Beyer, Anders (Aldershot Ashgate, 2001)
Extensive and generously illustrated interviews have been a feature of the lively Danish music periodical "Dansk Musik Tidsskrift" (Danish Music Review) since the 1960s. Now a long-standing tradition, these "conversations" with influential composers from all over the world are prepared by professional musicians and experienced writers on music. This volume is a collection of interviews selected from issues published since 1990 by Anders Beyer, the journal's editor-in-chief. The book gives an up-to-date picture of the North European musical perspectives through interviews with composers from each of the Nordic countries. These are further complemented by interviews with trend-setting composers from the rest of Europe and America. The interviews have been edited and translated into English to make them accessible to a wider audience. The volume features interviews with composers including Erik Bergman, Tikhon Chrennikov, Edison Denisov, Hans Gerfors, Philip Glass, Sofia Gubaidulina and Pelle Gudmundsen-Holmgreen.
Keywords: 20th Century (1901-2000); Composer; Avant-garde